Amavadin and Homologues as Mediators of Water Oxidation. Issue 4 (9th December 2015) - Domarus, Magdalena; Kuznetsov, Maxim L.; Marçalo, Joaquim; Pombeiro, Armando J. L.; da Silva, José Armando L.
Abstract: The vanadium(IV) N‐hydroxyiminodicarboxylate complexes [V(HIDPA)2 ] 2− and [V(HIDA)2 ] 2−, close models of the amavadin (a natural product from Amanita fungi lacking the V=O group but exhibiting a rare NO‐bound oxyiminate moiety), are shown to be the first recognized complexes of the early transition metals (up to periodic Group 7) that mediate the oxidation of water. The reactions were analyzed by visible spectrophotometry, mass spectrometry, and measurement of evolved dioxygen using Ce 4+ as sacrificial oxidant. A mechanism proposed on the basis of DFT calculations involves the reversible oxidation to the mononuclear V V ‐ON˙< center, where the redox active oxyimino group plays a key role and metal oxidation state variation is only one unit. The more similar model of the metallobiomolecule, [V(HIDPA)2 ] 2−, displays a lower oxidation rate than [V(HIDA)2 ] 2− but does not undergo appreciable degradation, in contrast to the latter. Abstract : Kept in the dark : Amavadin and related vanadium complexes are shown to be capable of promoting water oxidation under non‐photochemical conditions through a mechanism involving cooperation between the mononuclear metal center and ligands.